Regenerative agriculture through indigenous practice of using remains of livestock feed residues as a manure to boost groundnut productivity: Regenerative agriculture through indigenous practice of using remains of livestock feed residues as a manure to boost groundnut productivity - B S YENAGI; ROHINI SUGANDHI; B N MOTAGI; P NAGARAJU; D T KALLESH (Journal of Oilseeds Research, 2023)
Cow represents Mother Earth, as it is a source of goodness, its milk nourishes all creatures and dung is store house of millions of microorganisms’ acts as source of organic manure and her urine aids in decomposition of crop residues. It’s in practice for millennium but recently due to introduction of chemical fertilizer found to be disappearing in the farming community coupled with reduction in the livestock population. Application of manure prepared from livestock feed for four years resulted in mean groundnut pod yield of 1665 kg/ha as against application of FYM i.e., 1108 and control 818 kg/ha.